Biofilm morphology and microbiome of sequencing batch moving bed biofilm reactors treating cheese production wastewater. (February 2022) - Tsitouras, Alexandra; Butcher, James; Li, Jennifer; Stintzi, Alain; Delatolla, Robert
Abstract: Compact, on-site treatment of cheese production wastewater is required to meet increasing regulations. This study investigates the treatment of cheese production wastewater of a sequencing batch moving bed biofilm reactor (SB-MBBR); the effects of anaerobic staging times and aeration rates on biofilm morphology, dry-mass, thickness, mean dry-density, biomass viability, and microbiome. Increasing anaerobic staging time from 72 to 168 min improved carbon removal rates from 24.8 ± 0.5 to 41.6 ± 1.3 g·m −2 d −1, likely due to a rougher biofilm morphology, lower mean dry-density and therefore enhanced biofilm mass transport. The microbiome community shifts from a population dominated by denitrifiers and possibly putative polyphosphate accumulating organisms, Brachymonas, Dechloromonas, and Rhodoferax, to a lower abundance of fermenting bacteria with increasing anaerobic staging time and lower aeration. This study provides new evidence of polyphosphate accumulating organisms in SB-MBBRs treating cheese production wastewater, supporting the feasibility of the SB-MBBR for on-site treatment of carbon, nitrogen and phosphorous. Graphical abstract: Unlabelled Image Highlights: sCOD SARR increased with anaerobic staging (24.8 ± 0.5 to 41.6 ± 1.3 g·m −2 d −1 ) Biofilm thickness decreased (469.3 ± 39.9 to 258.97 ± 11.9 μm) with lower aeration Lower relative abundance of fermenters with longer anaerobic staging and aeration EBPR and putative PAOs (43.1 ± 8.4%) observed at lower aeration rates